Intergenerational Mobility in the Land of Inequality - Paolo Pinotti; Diogo G. C. Britto; Alexandre Fonseca; Breno Sampaio; Lucas Warwar (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
We provide the first estimates of intergenerational income mobility for a developing country, namely Brazil. We measure formal income from tax and employment registries, and we train machine learning models on census and survey data to predict informal income. The data reveal a much higher degree of persistence than previous estimates available for developed economies: a 10 percentile increase in parental income rank is associated with a 5.5 percentile increase in child income rank, and persistence is even higher in the top 5%. Children born to parents in the first income quintile face a 46% chance of remaining at the bottom when adults. We validate these estimates using two novel mobility measures that rank children and parents without the need to impute informal income. We document substantial heterogeneity in mobility across individual characteristics - notably gender and race - and across Brazilian regions. Leveraging children who migrate at different ages, we estimate that causal place effects explain 57% of the large spatial variation in mobility. Finally, assortative mating plays a strong role in household income persistence, and parental income is also strongly associated with several key long-term outcomes such as education, teenage pregnancy, occupation, mortality, and victimization.
Keywords: J62; D31; I31; R23; 330; Intergenerational Mobility; Inequality; Brazil; Migration; Place Effects